Strategi Pemasaran Digital Berbasis Influencer Marketing Dalam Meningkatkan Brand Engagement Di Kalangan Generasi Z - Erlangga Arya Sukmana (CV. SINAR HOWUHOWU, 2025)
The rapid development of digital technology has significantly transformed marketing strategies, particularly through the use of influencer marketing. Generation Z, as the most active group on social media platforms, has become the primary target for brands seeking to enhance brand engagement. This study aims to analyze the effectiveness of digital marketing strategies based on influencer marketing in increasing brand engagement among Generation Z. The research applies a descriptive approach by reviewing previous studies related to digital consumer behavior, influencer credibility, and user engagement forms. The findings indicate that influencer marketing positively contributes to increasing brand engagement through authentic, creative, and relevant content that aligns with the characteristics of Generation Z. Moreover, the selection of influencers whose values match the brand identity strengthens the emotional connection between consumers and brands. This study provides valuable insights for companies in designing more effective digital marketing strategies, particularly in the competitive landscape of social media.